The Antique Theme in Architectural and Sculptural Decor of Russian Sailing Ships - Tsekhanovskaia, Olga K. (Actual Problems of Theory and History of Art, 2015)
The present study focuses on the analysis of the décor of Russian sailing fleet during the period of the18th ‒ first half of the 19th centuries, namely using stories, motifs and heroes of ancient mythology. The author describes ships in terms of art history. In Russian art history ancient images in the ship’s decor have not previously been studied, though over a century and a half they were always in demand both in the titles and in the decoration of the ships. On Russian ships the main semantic accent was expressed in the decor located on the stern. The most popular subjects taken from the myths of ancient Greece are considered in the article. The sculptural compositions placed on the surface of the ship can tell us about the events taking place at that time in Russia. The author traces how the images of ancient heroes, ornaments were dependent on the prevailing art styles — baroque and classicism — and changed over one and a half century of sailing fleet history. On the basis of the historical and cultural analysis the prerequisites for the appearance of sculptural decor on Russian ships were traced and the influence of historical and cultural processes taking place in Russia on the features of development of the storylines in the architectural and sculptural decoration of the ships were determined. The comparative-descriptive method was used in analyzing and identifying the specific properties of the ship’s decor artistic expression. The research methodology is based on the study and systematization of theoretical and illustrative material, the analysis of the documents of Russian State Archive of the Navy, the collection of drawings, models of ships, models and authentic decor from the funds of the Central Naval Museum. Ancient stories were a great source of inspiration for the artists who decorated Russian sailing ships. The study of the ship’s décor allowed us to expand our knowledge of Russian applied arts of the 18th ‒ first half of the 19th century.